Students' perception of multiple dental visits for root canal treatment: Questionnaire-based study - Reem Siraj Alsulaimani; Kholod Al-Manei; Bashayer Baras; Razan Alaqeely; Ashraf El Metwally; Nahid Ashri (Wolters Kluwer Medknow Publications, 2016)
Introduction: Root canal treatment (RCT) is a meticulous procedure that requires focus and precision while working in a confined space such as the root canal system of the tooth. Hence, it is a challenging practice for dental students a questionnaire-based study was conducted to evaluate senior dental students' perception toward single- and multiple-visit RCT while considering tooth type and patient cooperation, and to identify the most common reasons for multiple-visit RCT. Materials and Methods: This cross-sectional study included 267 senior year dental students from three universities and one private college in Saudi Arabia. A self-administered questionnaire was distributed between May and October 2014. The questionnaire was divided into four main sections, which evaluated student perception regarding single- and multiple-visit treatment, patient cooperation, and the nontherapeutic reasons for multiple-visits treatment. The collected data were analyzed using SAS 9.3. Results: Two hundred and seventeen questionnaires were returned (response rate, 81%). Dental students perceive multiple-visit RCT for anterior and premolar teeth as a significantly more stressful event than multiple-visit RCT for molars (P < 0.0001; Bowker's test). Tooth type and patient medical status were the highest ranked reasons for multiple-visit RCT. The majority of the responders (90%) considered single-visit RCT for single-rooted teeth a positive practice. Conclusions: Multiple-visit RCT is a stressful event for dental students, especially if the treated tooth was a single-rooted tooth. Dental students are aware of the negative effect of multiple-visit treatment on patient compliance. Clinical training should consider single-visit treatment for single rooted teeth.